2018
DOI: 10.4324/9781315302430
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Space and Beyond

Abstract: Through the focus on organizational space, using the reception and significance of the seminal work on the subject by sociologist Henri Lefebvre, this book demonstrates why and how Lefebvre's work can be used to inform and elaborate organizational studies, especially in view of the current interest in the "socio-material" dimension of organizations.As the "spatial turn" in organizational research exposed the importance of spatial design in inducing power and cultural relations, Lefebvre's perspective has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…By analysing how techniques are created, controlled and selectively applied by corporations, Milton Santos explained the process Lefebvre (1991) referred to as the social production of the abstract space of capitalism. By shifting the focus from the embodied social space -as is the case in many applications of Lefebvre's work in organisation studies (Dale et al, 2018) -to personal relations with the territory, Santos identified the mechanisms that explain territorial fragmentation. Modern processes of urbanisation seek to create a single 'place' -understood here as shared norms -across various territories.…”
Section: Milton Santos: the Dialectics Of The Fragmented Territorymentioning
confidence: 99%
“…By analysing how techniques are created, controlled and selectively applied by corporations, Milton Santos explained the process Lefebvre (1991) referred to as the social production of the abstract space of capitalism. By shifting the focus from the embodied social space -as is the case in many applications of Lefebvre's work in organisation studies (Dale et al, 2018) -to personal relations with the territory, Santos identified the mechanisms that explain territorial fragmentation. Modern processes of urbanisation seek to create a single 'place' -understood here as shared norms -across various territories.…”
Section: Milton Santos: the Dialectics Of The Fragmented Territorymentioning
confidence: 99%